The role of marine biotoxins on the trophic transfer of Mn and Zn in fish - Pouil, Simon; Clausing, Rachel,; Metian, Marc; Bustamante, Paco; Dechraoui Bottein, Marie-Yasmine (Aquatic Toxicology, 2018)
International audience Essential nutrients are critical for physiological processes of organisms. In fish, they are obtained primarily from the diet, and their transfer and accumulation are known to be impacted by environmental variables such as water temperature, pH and salinity, as well as by diet composition and matrices. Yet, prey items consumed by fish may also contain toxic compounds such as marine toxins associated with harmful algae. These biotoxins have the potential to affect essential trace element assimilation in fish through chemical interactions such as the formation of trace element-toxin complexes or by affecting general fish physiology as in the modification of ion-specific transport pathways. We assessed the influence of dietary exposure to brevetoxins (PbTxs), ichthyotoxic neurotoxins produced by the dinoflagellate Karenia brevis, on trophic transfer of two essential trace elements, Mn and Zn, in a fish model. Using ecologically relevant concentrations of PbTxs and trace elements in controlled laboratory conditions, juvenile turbots Scophthalmus maximus were given food containing PbTxs before or at the same time as a feeding with radiotracers of the chosen essential elements (54 Mn and 65 Zn). Treatments included simultaneous exposure (PbTxs + 54 Mn + 65 Zn) in a single-feeding, 3-week daily pre-exposure to dietary PbTx followed by a single feeding with 54 Mn and 65 Zn, and a control (54 Mn and 65 Zn only). After a 21-day depuration period, turbot tissue brevetoxin levels were quantified and assimilation efficiencies of 54 Mn and 65 Zn were assessed. PbTxs were found in turbot tissues in each exposure treatment, demonstrating dietary trophic transfer of these toxins; yet, no differences in assimilation efficiencies of Mn or Zn were found between treatments or the control (p > 0.05). These results indicate that, in our experimental conditions, PbTx exposure does not significantly affect the trophic transfer of Mn and Zn in fish.